Learning styles as correlates of Grade 6 learner’s Mathematics performance in Buffalo City municipality in South Africa - Adu, Kemi O.; Pylman, Nicky; Adu, Emmanuel O. (Penerbit Universiti Kebangsaan Malaysia, 2020)
The poor academic achievement and negative attitude of learners towards Mathematics are not only influenced by teaching styles but the learning styles as well. In other words, the mismatches between teaching and learning styles have a way of raising its ugly head in affecting effective classroom interaction and hence leads to poor performance in Mathematics. Therefore, this study investigated the correlation between learning styles and Grade 6 Mathematics performance. The study adopted correlational research design of quantitative approach. The target population for this study are Grade 6 learners in Buffalo City education district. Stratified sampling was used to select 1225 Grade 6 learners. The finding shows that Grade 6 learners with visual learning style ( = 13.242, SD = 5.565) had the best performance in Mathematics at Buffalo City, followed by learners with auditory learning style ( = 12.996, SD = 3.883), and learners with Kinaesthetic learning style ( = 11.525, SD =3.800). It is recommended that teachers should be trained to know the different type of learning style exhibit by their learners to use them to impact knowledge and disseminate information to them since learning style could be described as a set of factors, behaviours and attitudes that facilitate learning for an individual in a given situation.